High levels of AXL expression in untreated EGFR‐mutated non‐small cell lung cancer negatively impacts the use of osimertinib. Issue 2 (11th November 2022) - Yoshimura, Akihiro; Yamada, Tadaaki; Serizawa, Masakuni; Uehara, Hisanori; Tanimura, Keiko; Okuma, Yusuke; Fukuda, Akito; Watanabe, Satoshi; Nishioka, Naoya; Takeda, Takayuki; Chihara, Yusuke; Takemoto, Shinnosuke; et al.
Abstract: For non‐small cell lung cancer (NSCLC) patients with epidermal growth factor receptor ( EGFR ) mutations, the initial therapeutic interventions will have crucial impacts on their clinical outcomes. Drug tolerant factors reportedly have an impact on EGFR‐tyrosine kinase inhibitor sensitivity. This prospective study investigated the impacts of drug tolerant‐related protein expression in tumors based on the efficacy of osimertinib in the first‐setting of EGFR ‐mutated advanced NSCLC patients. A total of 92 patients with EGFR ‐mutated advanced or postoperative recurrent NSCLC were analyzed and treated with osimertinib at 14 institutions in Japan. AXL, p53, and programmed death‐ligand 1 (PD‐L1) expression in patient tumors was determined using immunohistochemistry. The AXL signaling pathway was investigated using a cell line‐based assay and AXL‐related gene expression in The Cancer Genome Atlas (TCGA) database. High levels of AXL and positive‐p53 expression were detected in 26.1% and 53.3% of the pretreatment EGFR ‐mutated NSCLC tumors, respectively. High AXL expression levels were significantly associated with a shorter progression‐free survival compared with low AXL expression levels, irrespective of the EGFR activating mutation status ( p  = 0.026). Cell line‐based assays indicated that the overexpression of AXL protein accelerated PD‐L1 expression, which induced insensitivity to osimertinib. In the TCGA database, AXL RNA levels were positively correlated with PD‐L1 expression in the lung adenocarcinoma cohort. The results show that high AXL expression levels in tumors impact clinical predictions when using osimertinib to treat EGFR ‐mutated NSCLC patients. Trial Registration: UMIN000043942. Abstract : High levels of AXL and PD‐L1 expression predicts poor PFS with osimertinib. AXL protein overexpression induces PD‐L1 expression and osimertinib insensitivity. AXL expression in tumors impacts clinical predictions when using osimertinib.